Sentence structures of Indonesian and Tetun: a review in the context of BIPA in Timor Leste - Alexandre dos Reis; Nuny S. Idris; M. W. Rizkyanfi (ARKA INSTITUTE, 2026)
The purpose of this study is to analyze the comparative sentence structures of Indonesian (BI) and Tetun, and their implications for teaching Indonesian for Foreign Speakers (BIPA) in Timor Leste. This qualitative study utilizes a contrastive analysis method, with data consisting of sentence structures from both languages. The results show significant differences, particularly in the word order of possessive noun phrases and the use of grammatical particles. These differences have the potential to cause negative interference, which is a major source of difficulty for BIPA learners who are native Tetun speakers. The similarity in basic sentence patterns, such as the S-P-O structure, can facilitate the learning process. This research provides practical recommendations for BIPA instructors to develop teaching modules that focus on these areas of difficulty to enhance teaching effectiveness.